A new mutation for Cantu’s syndrome - Bargieł, Julia; Cabaj, Justyna; Tarkowska, Agata (Journal of Education, Health and Sport, 2022)
Introduction: Cantu syndrome is one of the rare genetic syndromes. Formally, there are no diagnostic criteria for Cantu syndrome, but given the characteristic appearance and reproducible features in people with a mutation in the ABCC9 gene, there is a conventional clinical picture that may suggest a diagnosis with high probability. This publication presents a case study of a two-week-old female patient who was qualified for genetic testing on the basis of her characteristic clinical picture. Whole exome sequencing revealed the presence of a mutation so far unknown in the human mutation database... Case report: A two-week-old patient was referred to the Neonatal Pathology Unit due to the features of the dysmorphic syndrome in order to extend the diagnosis. Biased family history: the child’s mother was diagnosed with hypogonadotrophic hypogonadism with suspected Kallman syndrome. The girl is very similar to her mother - in the physical examination, the following highlights: features of facial dysmorphia, a large, protruding tongue, excessive hair in the head and lumbar region. Due to the possibility of mutations in various genes correlating with Kallmann syndrome, a Whole Exome Sequencing (WES) study was commissioned. The study revealed the detection of a new Arg1116Pro mutation in the ABCC9 allele. Conclusions: In the presence of dimorphic features significant for Cantu syndrome, it is advisable to perform molecular genetic tests involving the use of a multigene panel. In the case of an uncertain clinical picture, it is worth performing Whole Exome Sequencing. Cantu’s syndrome is still a little-known disease that is often associated with the coexistence of many serious multi-system diseases. Therefore, it is crucial to make the diagnosis as early as possible in the patient’s life so that the patient is immediately provided with multidisciplinary medical care.